La aplicación del principio de subsidiariedad en la actividad económica del estado en el ordenamiento jurídico peruano - Cairampoma Arroyo, Alberto (2021)
This article addresses the principle of subsidiarity in the context of a social market economy. This is related to how the principle of subsidiarity has been interpreted and applied in our legal system. Since the change in the 1990s in the role of the State from provider to guarantor, and the incorporation of the principle of subsidiarity, its scope and limits have been questioned. The Peruvian Consumer Protection Authority—Indecopi, has been the one solving cases of possible violations of the principle of subsidiarity, and in this context has issued a "precedent of mandatory observance", which is extremely important to analyze so as to provide context to article 60 of the Peruvian Constitution.